IMF Survey, Volume 33, Issue 16. (IMF Survey; IMF Survey, 2004)
In July, the IMF's Independent Evaluation Office (IEO) released the findings of its review of the IMF-World Bank's Poverty Reduction Strategy Paper (PRSP) process and the IMF's Poverty Reduction and Growth Facility (PRGF).The main aims of the wide-ranging evaluation were to determine whether these two initiatives have been implemented according to original expectations and whether the IMF has been sufficiently supportive of the broader PRSP process. David Goldsbrough, Acting Director of the IEO, spoke with Jacqueline Irving of the IMF Survey about the report's findings.